Morphological parameters of image processing to characterize primary root emergence in evaluation of tomato seed vigor - de Oliveira, Gustavo Roberto Fonseca [UNESP]; de Salles, Felipe Kuhn Leão; Batista, Thiago Barbosa [UNESP]; da Silva, Marcio Souza; Cicero, Silvio Moure; Gomes-Junior, Francisco Guilhien (FapUNIFESP (SciELO), 2021)
The use of computational tools has become notable in seed quality control to assist in confirming seed lots of higher potential. Thus, the aim of this study was to use a computational approach to investigate analysis of morphological parameters that characterize primary root emergence in evaluation of tomato seed vigor. For that purpose, five seed lots were analyzed for germination and vigor (seedling emergence and analysis of seedling images). A parallel analysis of primary root emergence was made using computer-assisted imaging; the images recorded as germination proceeded were processed with the ImageJ® software to obtain aspect ratio and seed area parameters. Vigor differences among tomato seed lots can be identified based on primary root emergence, and computer image processing based on aspect ratio proves to be an efficient procedure to characterize emergence of the primary root in evaluation of tomato seed vigor.
Parâmetros morfológicos de processamento de imagens para caracterização da emergência da raiz primária na avaliação do vigor de sementes de tomate
Keywords: Aspect ratio; Computational to; Physiological potential; Solanum lycopersicum